WHAT DRIVES INVESTORS TO MAKE INVESTMENT DECISIONS? ANALYSIS OF HEURISTIC BIAS AND LONG-TERM ORIENTATION - Aksa, Baihaqi; Wijayanti, Dwi Marlina (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
This study aims to investigate the effect of heuristic biases such as overconfidence bias, availability bias, and representativeness bias on the investors’ investment decisions on the Indonesian stock exchange (IDX), as well as the moderating role of long-term orientation. By using a structured questionnaire, a total of 404 responses have been collected from individual investors who have made transactions in the Indonesian capital market, especially stocks. The relationships between variables were tested by applying the Structural Equation Modeling (SEM) method by using the SmartPLS 3.3.7 software. The results show that overconfidence bias, availability bias, and representativeness bias have a significant and positive effect on investors' investment decisions. Meanwhile, the moderating effect of long-term orientation is significant only on the effect of overconfidence bias on investment decisions. This shows that the long-term orientation of investors strengthens the effect of overconfidence bias on investment decisions. Information availability bias and representativeness bias in this study have no significant moderating effect of long-term orientation. This research is expected to be able to provide new insights about the role of heuristic bias in individual investors' investment decisions in the stock market.